Analysis of the Influence of the Idea of a Closed Electoral System on Citizen Political Participation - Rasji Rasji; Arief Dermawan Singhs; Dave Hamonangan (CV. Rayyan Dwi Bharata, 2023)
The choice of an electoral system is fundamentally more of a political process and considerations of political advantage are almost always a factor in the choice of an electoral system. Furthermore, the electoral system itself is divided into two, namely an open proportional system and a closed proportional system. With an open proportional system, citizens can specifically choose their parties and candidates for the legislature. Meanwhile, in a closed proportional system, citizens can only vote for a party, later the party leader has the right to determine the party's legislative candidates. The author describes that a closed proportional electoral system has advantages and disadvantages. This system has the advantage that applying a closed proportional system can later reduce the campaign budget, so there is no need to waste too much money. However, on the other hand, this system has drawbacks, namely that this system receives a lot of rejection from citizens who feel that this system is unfair and can open up a wide space for party leaders to commit all acts of fraud. Basically whichever system is chosen will have a tendency towards one of these two goals. A closed electoral system affects the political participation of citizens. The reason is, this idea has reaped a lot of rejection by citizens because they feel that this system will open the door to fraud for party rulers and later candidates for legislative members can be more inclined to their party leaders and not to citizens, because they feel that those who elect them are party leaders.